The Wnt Signaling Antagonist Kremen1 is Required for Development of Thymic Architecture. Issue 2 (2006) - Osada, Masako; Ito, Emi; Fermin, Hector A.; Vazquez-Cintron, Edwin; Venkatesh, Tadmiri; Friedel, Roland H.; Pezzano, Mark
Abstract : Wnt signaling has been reported to regulate thymocyte proliferation and selection at several stages during T cell ontogeny, as well as the expression of FoxN1 in thymic epithelial cells (TECs). Kremen1 (Krm1) is a negative regulator of the canonical Wnt signaling pathway, and functions together with the secreted Wnt inhibitor Dickkopf (Dkk) by competing for the lipoprotein receptor-related protein (LRP)-6 co-receptor for Wnts. Here krm1 knockout mice were used to examine krm1 expression in the thymus and its function in thymocyte and TEC development. krm1 expression was detected in both cortical and medullary TEC subsets, as well as in immature thymocyte subsets, beginning at the CD25+CD44+ (DN2) stage and continuing until the CD4+CD8+(DP) stage. Neonatal mice show elevated expression of krm1 in all TEC subsets. krm1 − / − mice exhibit a severe defect in thymic cortical architecture, including large epithelial free regions. Much of the epithelial component remains at an immature Keratin 5 + (K5) Keratin 8 + (K8) stage, with a loss of defined cortical and medullary regions. A TOPFlash assay revealed a 2-fold increase in canonical Wnt signaling in TEC lines derived from krm1 − / − mice, when compared with krm1 + / + derived TEC lines. Fluorescence activated cell sorting (FACS) analysis of dissociated thymus revealed a reduced frequency of both cortical (BP1 + EpCAM + ) and medullary (UEA-1 + EpCAM hi ) epithelial subsets, within the krm1 − / − thymus. Surprisingly, no change in thymus size, total thymocyte number or the frequency of thymocyte subsets was detected in krm1 − / − mice. However, our data suggest that a loss of Krm1 leads to a severe defect in thymic architecture. Taken together, this study revealed a new role for Krm1 in proper development of thymic epithelium.